Perennial grassland agriculture restores critical ecosystem functions in the U.S. Upper Midwest - Wepking, Carl; Mackin, Hunter C.; Raff, Zach; Shrestha, Debendra; Orfanou, Anna; Booth, Eric G.; Kucharik, Christopher J.; Gratton, Claudio; Jackson, Randall D. (Frontiers in Sustainable Food Systems, 2022)
Dominant forms of agricultural production in the U.S. Upper Midwest are undermining human health and well being. Restoring critical ecosystem functions to agriculture is key to stabilizing climate, reducing flooding, cleaning water, and enhancing biodiversity. We used simulation models to compare ecosystem functions (food-energy production, nutrient retention, and water infiltration) provided by vegetation associated with continuous corn, corn-soybean rotation, and perennial grassland producing feed for dairy livestock. Compared to continuous corn, most ecosystem functions dramatically improved in the perennial grassland system (nitrate leaching reduced 90%, phosphorus loss reduced 88%, drainage increased 25%, evapotranspiration reduced 29%), which will translate to improved ecosystem services. Our results emphasize the need to incentivize multiple ecosystem services when managing agricultural landscapes.